Assessment of plant species diversity and abundance using line-transect method at Pantai Sabak, Kelantan (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Coastal areas are environmentally sensitive areas filled with various local inhabitants focusing on the tree species ecosystem continuing to develop according to its environment. Pantai Sabak is one of the well-known eroded beaches in Kelantan due to the natural phenomenon, tidal wave erosion. This study aimed to identify the species availability and determine the species abundance, density, frequency, and diversity found in Pantai Sabak, Kelantan. Certain native species and common tree species at the coastline area are still available, such as Nypa fruticans and Ipomoea pes-caprae. Shocking results are achieved whereby the shoreline area has been degraded by the tidal wave and shoving away some species such as Cocos nucifera. Due to the situation, the coastal area has reached the mangrove area resulted in the species along the transect line is mangrove species namely Excoecaria agallocha. Another species achieved were shrubs and it showed Pantai Sabak has been severely damaged. A total of 1,350 individuals of 30 species from 30 genera belong to 22 families were recorded along two kilometres transect line. By using the diversity index which is Shannon-Wiener Diversity Index (H’) value is 2.99, Shannon-Wiener Maximum Index (H’max) is 3.40 while Shannon Evenness (EH) is 0.88. These results showed the area of the study is still diverse in species hence dominated by shrubs such Lantana camara. Hence, this study only focuses on the species diversity ecosystem, not the causes of the occurrence that occurred.
Keywords: coastal area; plant species; abundance; line transect; diversity index